Oral mucous membrane pemphigoid - Two case reports with varied clinical presentation - Sreedevi Dharman; Arvind Muthukrishnan (Wolters Kluwer Medknow Publications, 2016)
Mucous membrane pemphigoid (MMP) is a heterogeneous group of autoimmune chronic inflammatory, subepithelial blistering disorder, predominantly involving the mucous membranes. It has a female predilection and commonly occurring after the fifth decade of life. The oral mucosa is affected in more than 90% of cases. Dentists could be the first health personnel to identify and diagnose this rare mucocutaneous lesion. Two unique cases of oral MMP with varied clinical presentation, the diagnostic modality, treatment and follow-up are presented.